Characterization of large deletions in the F8 gene using multiple competitive amplification and the genome walking technique. Issue 6 (3rd July 2013) - You, G. L.; Ding, Q. L.; Lu, Y. L.; Dai, J.; Xi, X. D.; Wang, X. F.; Wang, H. L.
Summary Background Large deletions in the F8 gene are responsible for approximately 3% of severe hemophilia A (HA) cases. However, only a few breakpoints in large deletions have been characterized. Objectives To identify large deletions in the F8 gene and to characterize the molecular mechanisms leading to these deletions. Patients and methods We used AccuCopy technology, a copy number variation (CNV) genotyping method based on multiplex competitive amplification, to confirm deletions in index patients and to screen potential female carriers in 10 HA families. Also, breakpoints of these large deletions were characterized by a primer walking strategy and genome walking technique. Results Ten large deletions and four female carriers were identified by AccuCopy. The extents of deleted regions ranged from 1.3 to 68.5 kb. Exact breakpoints of these deletions were successfully characterized. Eight of them presented microhomologies at breakpoint junctions and several recombination‐associated elements (repetitive elements, non‐B conformation forming motifs and sequence motifs) were also observed in close proximity to the junctions. Conclusions AccuCopy technology is a reliable and efficient tool for detecting large deletions in the F8 gene and identifying HA female carriers. The genome walking technique is a highly specific, efficient and versatile method for characterizing the deletion breakpoints. Molecular characterization of deletion breakpoints revealed that non‐homologous end joining and microhomology‐mediated replication‐dependent recombination were the major causative mechanisms of the 10 large deletions in the F8 gene.